Deutsche und italienische „geschlechtersensible Sprache“ zwischen rechtlicher und institutioneller Kommunikation - Brambilla, Marina; Crestani, Valentina (Linguistik Online, 2024)
The article explores the use of human nouns in a corpus of directive texts (legal texts on gender equality and on equality of people with disabilities) and the conceptualisation of gender-sensitive language in a corpus of advisory texts (i. e. in manuals on legal and administrative language and in gender guidelines of universities) produced in Germany and in Italy. The contrastive analyses of the directive and advisory texts are closely linked: namely, gender guidelines that universities make available on their web pages refer to legal texts and to manuals. After theoretical and methodological clarifications, the article reports the main results of the two analyses, which can be summarised as follows: - Directive texts: both in Italian legal texts on gender equality and on equality of people with disabilities there is a high percentage of masculine forms, while the German legal text on gender equality has a high percentage of feminine nouns and the German legal texts on equality of people with disabilities have a high percentage of gender-inclusive nouns (such as epicene nouns). - Advisory texts: German manuals on legal and administrative texts recommend the use of gender-sensible language, particularly when referring to natural persons, i. e. avoiding the use of generic masculines. Italian manuals on administrative texts recommend avoiding generic masculines. German and Italian recommendations also share a binary view. The situation is different in advisory texts produced by Universities: German guidelines (although not all of them) give both advice on binary forms and on overcoming this linguistic binarism, whereas Italian ones recommend binary forms and focus on the construction of feminine nouns. The use of masculine nouns for men and feminine nouns for women, neutral forms, and alternative constructions (such as passive forms), on the other hand, is a common feature of German and Italian guidelines.